2019
DOI: 10.1111/ncmr.12148
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup Conflict 2020

Abstract: The pervasiveness, persistence, and petrifying scope of intergroup conflict have fueled substantial scholarly interest in intergroup conflict across the social and biological sciences. Here we outline five questions that we hope students of intergroup conflict will undertake to research in years to come: (a) When and why do people engage in, and publicly display, blatant forms of intergroup hostility? (b) How do different moral motives shape individual behavior in intergroup conflict? (c) How do intragroup pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 120 publications
(132 reference statements)
0
16
0
Order By: Relevance
“…The project literature helps us understand the implications of this attention perspective within and across teams on individual and team behavior. This literature concedes that projects that focus on their sole effectiveness through pursuing their independent goals are often those that succeed (Martinsuo, 2013), because allegiances and misalignment of goals across teams may limit the effectiveness of MTM on any single project (Halevy & Cohen, 2019; Mesmer-Magnus, Carter, Asencio, & DeChurch, 2016). For example, a recent study demonstrated that when developers discuss multiple projects simultaneously, the average amount of time to resolve an issue declines; however, this discussion-switching can hurt the resolution time of a single project (Hu, Wang, Chang, Yin, & Zhang, 2018).…”
Section: Outcomes Of Mtmmentioning
confidence: 99%
“…The project literature helps us understand the implications of this attention perspective within and across teams on individual and team behavior. This literature concedes that projects that focus on their sole effectiveness through pursuing their independent goals are often those that succeed (Martinsuo, 2013), because allegiances and misalignment of goals across teams may limit the effectiveness of MTM on any single project (Halevy & Cohen, 2019; Mesmer-Magnus, Carter, Asencio, & DeChurch, 2016). For example, a recent study demonstrated that when developers discuss multiple projects simultaneously, the average amount of time to resolve an issue declines; however, this discussion-switching can hurt the resolution time of a single project (Hu, Wang, Chang, Yin, & Zhang, 2018).…”
Section: Outcomes Of Mtmmentioning
confidence: 99%
“…Social media users tend to interact with like-minded people through which group formation takes shape (Bennett & Segerberg, 2011), but social media platforms also provide a space for people from different backgrounds to encounter one another (Del Vicario et al, 2016). In cases of contentious political issues, such encounters can lead to intergroup conflict: an antagonistic pattern of interaction between online communities (Halevy & Cohen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the fourth paper, Nir Halevy and Taya Cohen identify key pressing research questions and challenges for the field of intergroup conflict. The first question the authors pose is “When and why do people engage in, and publicly display, blatant forms of intergroup hostility?” They identify some antecedents of intergroup hostility that have achieved ample attention in the literature, such as relative deprivation, direct threats to group interests, and perceived threats.…”
mentioning
confidence: 99%